2020
DOI: 10.1016/j.xfre.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA fragmentation index and high DNA stainability do not influence pregnancy success after intracytoplasmic sperm injection

Abstract: Objective: To evaluate the ability of sperm DNA fragmentation index (DFI) and high DNA stainability (HDS) to influence the chance of achieving pregnancy in couples undergoing intracytoplasmic sperm injection (ICSI) cycles. Design: A retrospective study evaluating couples who underwent an ICSI cycle between 2009 and 2018. Setting: Reproductive center. Patient(s): Consecutive couples who underwent an ICSI cycle and had a semen analysis with subsequent DFI and HDS testing, evaluated using Sperm Chromatin Structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Three of the four studies showed a significant difference (p<0.01) in favor of APA increasing DNA fragmentation, even among normozoospermic males [ 21 22 24 ]. All six studies examining DNA fragmentation between fertile and infertile males with proven primary or secondary infertility, which reported a significant difference in favor of increasing DNA fragmentation with APA [ 25 26 27 28 29 30 ]. Four studies examined males with proven primary or secondary infertility [ 31 32 33 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the four studies showed a significant difference (p<0.01) in favor of APA increasing DNA fragmentation, even among normozoospermic males [ 21 22 24 ]. All six studies examining DNA fragmentation between fertile and infertile males with proven primary or secondary infertility, which reported a significant difference in favor of increasing DNA fragmentation with APA [ 25 26 27 28 29 30 ]. Four studies examined males with proven primary or secondary infertility [ 31 32 33 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were at high risk of applicability concerns in domain “reference standard” when the patient's age category threshold is not comparable to the thresholds of other studies. Overall, the domain “index test” was considered to be at “low risk” because there were 10 studies that utilized TUNEL assay [ 21 23 25 26 27 31 32 33 38 39 ], 6 studies utilizing SCSA [ 22 28 30 34 35 37 ], 1 study using Comet assay [ 36 ], and 2 studies that utilized the SCD to quantify DNA fragmentation [ 24 29 ].…”
Section: Resultsmentioning
confidence: 99%